MANAGEMENT OF THE REX BIREUEN BUSINESS AREA ACCORDING TO THE CONCEPT OF ISLAMIC ECONOMIC LAW - Riza, Nauval; Hasan, Badri; Adnan, Boihaqi (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This research aims to analyze the management of Bireuen Rex Area and its results based on Bireuen Regency Qanun No. 1 of 2019 concerning the Management of Regional Property (BMD) by applying the concept of Milk Al-Daulah. This Qanun regulates various aspects related to BMD management, including planning, procurement, utilization, supervision, and control of regional property assets. This research is a field research, which is conducted by collecting data at the location of the object of research, which is the primary data source in the research. Data is obtained through document review, interviews with relevant government officials, and direct observation in the field. The results show that the management of Rex Bireuen Area has been carried out in accordance with the provisions stipulated in Qanun No. 1 of 2019, including systematic planning, transparent procurement, and effective utilization to increase regional income. The implementation of the Milk Al-Daulah concept can be seen in the management that emphasizes public interest, transparency, accountability, efficiency, and justice. The land and assets in the Rex Area are managed by the local government to ensure maximum benefits for the community, with strict supervision to prevent misuse of assets. This research concludes that the management of the Bireuen Rex Estate has fulfilled the principles of Milk Al-Daulah, which underlines the importance of state ownership of public assets for the welfare of the community.